Seeing beneath the soil : bprospecting methods in archaeology - Clark, Anthony (Anthony J.) (Taylor & Francis e-Library, 2003)
Dr. Clark, who was one of the earliest to work in this field, and has written the first general survey of an increasingly important area of practical archaeology.